Effects of surface application of calcium-magnesium silicate and gypsum on soil fertility and sugarcane yield - Costa Crusciol, Carlos Alexandre [UNESP]; Foltran, Rodrigo [UNESP]; Rossato, Otavio Bagiotto [UNESP]; McCray, James Mabry; Rossetto, Raffaella (Soc Brasileira de Ciência do Solo, 2014)
Lime application recommendations for amendment of soil acidity in sugarcane were developed with a burnt cane harvesting system in mind. Sugarcane is now harvested in most areas without burning, and lime application for amendment of soil acidity in this system in which the sugarcane crop residue remains on the ground has been carried out without a scientific basis. The aim of this study was to evaluate the changes in soil acidity and stalk and sugar yield with different rates of surface application of calcium, magnesium silicate, and gypsum in ratoon cane. The experiment was performed after the 3rd harvest of the variety SP 81-3250 in a commercial green sugarcane plantation of the Sao Luiz Sugar Mill (47 degrees 25'33 ''W; 21 degrees 59'46 ''S), located in Pirassununga, Sao Paulo, in southeast Brazil. A factorial arrangement of four Ca-Mg silicate rates (0, 850, 1700, and 3400 kg ha(-1)) and two gypsum rates (0 and 1700 kg ha(-1)) was used in the experiment. After 12 months, the experiment was harvested and technological measurements of stalk and sugar yield were made. After harvest, soil samples were taken at the depths of 0.00-0.05, 0.05-0.10, 0.10-0.20, 0.20-0.40, and 0.40-0.60 m in all plots, and the following determinations were made: soil pH in CaCl2, organic matter, P, S, K, Ca, Mg, H+ Al, Al, Si, and base saturation. The results show that the application of gypsum reduced the exchangeable Al3+ content and Al saturation below 0.05 m, and increased the Ca2+ concentration in the whole profile, the Mg2+ content below 0.10 m, K+ below 0.4 m, and base saturation below 0.20 m. This contributed to the effect of surface application of silicate on amendment of soil acidity reaching deeper layers. From the results of this study, it may be concluded that the silicate rate recommended may be too low, since the greater rates used in this experiment showed greater reduction in soil acidity, higher levels of nutrients at greater depths and an increase in stalk and sugar yield.

As recomendações de corretivos de acidez em cana-de-açúcar foram desenvolvidas em sistema de colheita com cana queimada. Hoje, a maioria das áreas é colhida sem queima. Nesse novo sistema de colheita, em que o resíduo da colheita permanece na superfície do solo, a aplicação superficial de corretivos de acidez realiza-se sem embasamento científico. O objetivo deste estudo foi avaliar a alteração da acidez do solo e a produtividade de colmos e açúcar com a aplicação superficial de doses de silicato de cálcio-magnésio e gesso agrícola em cana-soca. O experimento foi realizado após a 3ª colheita da variedade SP 81-3250, em uma plantação comercial de cana crua da Usina São Luiz (47º 25' 33" W, 21º 59' 46" S), localizada em Pirassununga, Estado de São Paulo. O experimento foi montado em um arranjo fatorial com quatro doses de silicato de cálcio-magnésio (0, 850, 1.700 e 3.400 kg ha-1) e duas doses de gesso agrícola (0 e 1.700 kg ha-1). Após 12 meses, o experimento foi colhido e determinada a produtividade de colmos e açúcar. Após a colheita, amostras de solo foram retiradas nas profundidades de 0,00-0,05, 0,05-0,10, 0,10-0,20, 0,20-0,40 e 0,40-0,60 m em todas as parcelas, e realizadas as seguintes determinações: pH em CaCl2, matéria orgânica, P, S, K, Ca, Mg, H+Al, Al, Si e saturação por bases. A aplicação de gesso agrícola reduziu os teores de Al3+ e a saturação por Al abaixo de 0,05 m e aumentou o teor de Mg2+ abaixo de 0,10 m, a concentração de Ca2+ em todo o perfil, a concentração de K+ abaixo de 0,4 m e a saturação por bases abaixo dos 0,20 m. Isso contribuiu para que o efeito da aplicação superficial de silicato na alteração da acidez do solo atingisse camadas mais profundas. A partir dos resultados deste estudo, pode-se concluir que a dose de silicato recomendada pode ser insuficiente, já que as maiores doses utilizadas neste experimento propiciaram maior redução da acidez do solo, níveis mais elevados de nutrientes em profundidade e aumento na produtividade de colmos e açúcar.
Efeito da aplicação superficial de silicato de cálcio-magnésio e de gesso na fertilidade do solo e produtividade da cana-de-açúcar
Keywords: Soil acidity correction; Silicon; Stalk and sugar yield; Green sugarcane; Correção de acidez do solo; Silício; Produtividade de colmos e açúcar; Cana crua